& I, the Moment of being Dis-Stance Together: Research into Online Performance Design for the Interplay between Intangible and Tangible Cultural Heritage - Wu, Yi-Chen (Mimesis Journal, 2024)
The article employs a practice-as-research approach in scenography to re-imagine theatre space as a space that is opened through the process of moving towards the availability of things. It focuses on the creative process of the author’s online theatre piece, & I, the Moment of being Dis-Stance Together (2023), to explore the transition of scenography to online performance design that devises mixed reality performance and also delves into how Chinese philosophical concepts from the Book of Changes offer alternative interpretations of this genre of work.